2017
DOI: 10.4293/jsls.2017.00032
|View full text |Cite
|
Sign up to set email alerts
|

The Routine Use of Cholangiography for Laparoscopic Cholecystectomy in the Modern Era

Abstract: Background and Objectives:The use of routine versus selective intra-operative cholangiogram (IOC) for laparoscopic cholecystectomy (LC) remains an area of debate. In this study, we investigated the routine use of IOC in a single center, to determine whether it confers a reduced risk of common bile duct (CBD) injury and improved patient outcomes. We also identified several preoperative predictive factors for CBD stone detection on IOC to investigate the feasibility of a predictive model.Methods:We identified 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
0
18
1
Order By: Relevance
“…The most common complication was wound infection (N=2) followed by equal frequencies of intraabdominal collection, pancreatitis, bile leak, bleeding, and postoperative hernia (N=1). Similarly, Photi et al found that wound infection was the most common postoperative complication, followed by bleeding, sepsis, bile leak, and pancreatitis (23) . The higher frequency of wound infection in the latter study is explained by their larger sample size (1005), compared to ours (56).…”
Section: Discussionmentioning
confidence: 92%
“…The most common complication was wound infection (N=2) followed by equal frequencies of intraabdominal collection, pancreatitis, bile leak, bleeding, and postoperative hernia (N=1). Similarly, Photi et al found that wound infection was the most common postoperative complication, followed by bleeding, sepsis, bile leak, and pancreatitis (23) . The higher frequency of wound infection in the latter study is explained by their larger sample size (1005), compared to ours (56).…”
Section: Discussionmentioning
confidence: 92%
“…A selective policy of IOC use was adopted in 14 studies with a mean IOC use of 16.7% (2.8%–36.9%) in 12,064 patients [ 18 , 19 , 34 , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] ]. Additionally, 14 studies adopted a policy of routine IOC with a mean average use of 88.3% (63.5%–99.2%) in 25,072 patients [ 17 , 19 , 34 , 37 , 42 , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] ].…”
Section: Resultsmentioning
confidence: 99%
“…Although the overall detection rate of CBD stones is low (5.8%), confirmed by subsequent ERCP, no patients in our cohort were readmitted with CBD stones. The reported incidence of CBD stones varied between 8-15% [8][9][10][11]. Furthermore, preoperative investigations are not predictive of negative IOC with some patients having filling defects on IOC despite nonsuggestive preoperative findings.…”
Section: Discussionmentioning
confidence: 99%